Menyatukan Derap Langkah: Membangun Visi Kolektif untuk Mewujudkan Pariwisata Berkelanjutan di Desa Liyu Kabupaten Balangan - Riyadi, Muhammad Dicky; Hamid, Ismar; Husna, Rabiyatul; Yani, Yeltika Indri; Selvania, Repita; RIzky, Muhammad; Hairunnisa; Assyifa, Calista Nur; Melani, Andi Mauritta; Maulida, Marcelly Rizky; Mauliya, Meilinda Dwiyanti; Angelina, Zahrani Dhea; Gufran, Muhammad; Irsan (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
This community service program was carried out in Liyu Village, Halong District, Balangan Regency and lasted for 57 days, from July 17 to September 11, 2025. This activity aims to address the main issues in village tourism development, namely the lack of a shared vision among stakeholders, including the village government, business actors, and the community. This difference in perception has resulted in low community participation, economic inequality, and weak coordination in tourism management. The technique used in this study is qualitative descriptive, using the live-in method and the pentagonal asset concept. The pentagonal asset concept was used to solve the problems that arose and create goals that would later be processed into programs according to the village's needs. The activities of this program included field observations, village discussions, and socialization on the importance of synergy among all elements of the village. Through open dialogue forums, the community was invited to express their aspirations, explore local potential, and formulate directions for sustainable tourism development. The results of the activities showed an increase in the collective awareness of the community regarding the importance of cross-sector collaboration, the formation of a shared vision for tourism management, and the creation of a communication forum between stakeholders as a platform for ongoing coordination. The obstacles encountered included the limited time available for residents to attend and a culture of reluctance to express opinions. Nevertheless, this activity succeeded in strengthening the community's sense of ownership of their village's potential and encouraged the formation of a collective commitment to manage tourism in a fair, transparent, and sustainable manner. In conclusion, the alignment of vision through a participatory approach has proven to be effective as a foundation for strengthening sustainable tourism governance in Liyu Village.